ANALYSIS OF THE DESIGN OF A WEBSITE-BASED POINT OF SALES SYSTEM FOR HOTEL MANAGEMENT - Wijaya, Komang Mahayuni Chikara; Utama, I Wayan Nanda Asa; Rukmiyati, Ni Made Sri; Tuwi, I Wayan; Susanti, Christina (Transpublika Publisher, 2025)
This research aims to design and develop an efficient and integrated website-based Point of Sales (POS) system for Kamala Bali Resort in Nusa Dua, in order to improve operational efficiency and service quality. The method used is a qualitative approach, which includes in-depth interviews, direct observation, and document analysis to understand the needs and challenges faced by the resort in managing the transaction system. The results showed that the development of a website-based POS system that integrates the Front Office Cashier (FOC) and Restaurant Bar Cashier (RBC) modules can accelerate the guest registration process, food and beverage order management, and real-time financial transaction management. The system also reduces the risk of human error and increases the transparency of financial reports. The contribution of this research is not only to provide practical solutions for small and medium-sized hotels in adopting technology, but also to enrich the literature regarding the application of information systems in the hospitality industry, as well as to become a model for other hotels in Indonesia that want to transform into the digital era.